The Gift of the Dying: The Tragedy of AIDS and the Welfare of Future African Generations - Young, A. (Quarterly Journal of Economics, 2005)
This paper simulates the impact of the AIDS epidemic on future living standards in South Africa. I emphasize two competing effects. On the one hand, the epidemic is likely to have a detrimental impact on the human capital accumulation of orphaned children. On the other hand, widespread community infection lowers fertility, both directly, through a reduction in the willingness to engage in unprotected sexual activity, and indirectly, by increasing the scarcity of labor and the value of a woman's time. I find that even with the most pessimistic assumptions concerning reductions in educational attainment, the fertility effect dominates. The AIDS epidemic, on net, enhances the future per capita consumption possibilities of the South African economy.